Pembentukan niat pembelian ulang konsumen pada e-commerce: Peran kepuasan, kepercayaan, nilai yang dirasakan, dan pengalaman daring - Windy Fasmita; Hetty Karunia Tunjungsari (Universitas Tarumanagara, 2026)
This study aims to examine the factors influencing repurchase intention in the e-commerce sector, with particular emphasis on the roles of e-satisfaction, e-trust, perceived value, and prior online experience. Despite the rapid expansion of e-commerce in Indonesia, maintaining consumer loyalty remains a significant challenge, as the growth in transaction value does not necessarily correspond with increased customer retention. Employing a quantitative research design, data were collected through an online questionnaire distributed to 331 respondents who had engaged in online shopping activities within the past six months. The data were subsequently analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the assistance of SmartPLS4 software. The findings reveal that e-trust and perceived value exert a significant positive influence on repurchase intention. In contrast, e-satisfaction was found to have no significant effect on consumers’ intention to repurchase. Furthermore, prior online experience was identified as a mediating factor that strengthens the relationship between e-trust, perceived value, and repurchase intention while no mediation effect was observed in the relationship involving e-satisfaction. These results suggest that, within the contemporary e-commerce environment, consumer trust and value perception play a more substantial role than satisfaction in encouraging repeat purchase behavior. Penelitian ini bertujuan untuk menganalisis pengaruh kepuasan elektronik, kepercayaan elektronik, nilai yang dirasakan dan pengalaman daring sebelumnya terhadap niat pembelian ulang pada sektor e-commerce. Meskipun pertumbuhan e-commerce di Indonesia terus meningkat, mempertahankan loyalitas konsumen masih menjadi tantangan bagi perusahaan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei terhadap 331 responden yang pernah berbelanja melalui e-commerce dalam enam bulan terakhir. Data dianalisis menggunakan software Partial Least Squares Structural Equation Modeling (PLS-SEM) dengan bantuan SmartPLS 4. Hasil penelitian menunjukkan bahwa kepercayaan elektronik dan nilai yang dirasakan berpengaruh positif dan signifikan terhadap niat pembelian ulang, sedangkan kepuasan elektronik tidak berpengaruh signifikan. Selain itu, pengalaman daring sebelumnya terbukti memediasi hubungan antara kepercayaan elektronik dan nilai yang dirasakan terhadap niat pembelian ulang, namun tidak memediasi hubungan antara kepuasan elektronik dan niat pembelian ulang. Temuan ini menunjukkan bahwa kepercayaan konsumen dan persepsi nilai memiliki peran yang lebih besar dibandingkan kepuasan dalam mendorong pembelian ulang pada e-commerce.